Mobilities in ambipolar field effect transistors based on single-walled carbon nanotube network and formed on a gold nanoparticle template - Chalao Wongsaeng (2018)
Ambipolar field effect transistors based on a single-walled carbon nanotube (SWNT) network formed on a gold nanoparticle (AuNP) template with polyvinyl alcohol as a gate insulator were studied by measuring the current-gate voltage characteristics. It was found that the mobilities of holes and electrons increased with increasing AuNP number density. The disturbances in the flow pattern of the carbon feedstock in the chemical vapor deposition growth that were produced by the AuNP geometry, resulted in the differences in the crystallinity and the diameter, as well as the changes in the degree of the semiconductor behavior of the SWNTs. © 2014 AIP Publishing LLC.